Application Of Health Belief Model: Perception And Knowledge Of Body Weight Management And The Effectiveness Of Educational Intervention On Weight Control Intention Among Malaysians - Raman, Sivasankari (2024)
Obesity and overweight have become major health concerns over the past 50 years, increasing the risk of illness, affecting the quality of life and raising financial burdens worldwide. This study aims to investigate the perception and knowledge of body weight management and to explore the weight control intention by an online educational intervention using the Health Belief Model (HBM).